Effects of indium on the intermetallic layer between low-Ag SAC0307-xIn lead-free solders and Cu substrate - Kanlayasiri, Kannachai; Sukpimai, Kamtorn (My University, 2016)
This research has investigated the effects of indium on the intermetallic layer formation attributable to the reaction between low-Ag SAC0307-xIn lead-free solder and a Cu substrate, where x = 0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 wt%. This study has also examined the post-soldering and post-thermal aging interfacial layers. Morphology parameters were utilized to represent the shape of total intermetallic layer at the interface. The findings indicated that indium had no effect on the pre- and post-aging intermetallic layer overall thicknesses but lowered the Cu3Sn/Cu6Sn5 thickness ratio; and that the concentrations of indium exhibited no influence over the post-soldering and post-thermal aging morphology parameter values. In the experiments, the morphology parameter value decreased with increase in the aging time. In addition, the suppression effect of indium on the growth of Cu3Sn layer was evident in the post-thermal aging stage with the growth inversely correlated to the indium content. Discussion on the suppression mechanism of indium on the Cu3Sn formation is also provided herein.
Keywords: Interface; Intermetallics; Lead-free solder; Metals and alloys